Suprachiasmatic neuron numbers and rest-activity circadian rhythms in older humans - Wang, Joshua L.; Lim, Andrew S.; Chiang, Wei-Yin; Hsieh, Wan-Hsin; Lo, Men-Tzung; Schneider, Julie A.; Buchman, Aron S.; Bennett, David A.; Hu, Kun; Saper, Clifford B. (Annals of neurology, 2015)
The suprachiasmatic nucleus (SCN) of the hypothalamus, the master mammalian circadian pacemaker, synchronizes endogenous rhythms with the external day–night cycle. Older humans, particularly those with Alzheimer disease (AD), often have difficulty maintaining normal circadian rhythms compared to younger adults, but the basis of this change is unknown. We report that the circadian rhythm amplitude of motor activity in both AD subjects and age‐matched controls is correlated with the number of vasoactive intestinal peptide–expressing SCN neurons. AD was additionally associated with delayed circadian phase compared to cognitively healthy subjects, suggesting distinct pathologies and strategies for treating aging‐ and AD‐related circadian disturbances. Ann Neurol 2015;78:317–322